Exploring location factors of logistics facilities from a spatiotemporal perspective: A case study from Shanghai. (April 2022) - Yang, Zhiwei; Chen, Xiaohong; Pan, Ruixu; Yuan, Quan
Abstract: In the era of economic globalization and the e-commerce boom, the demand for urban logistics has been rapidly growing in terms of both scale and intensity. The spatial clustering of logistics facilities and their associated environmental consequences has caused growing concern. This study analyzes the spatial evolution of logistics facilities and establishes a series of regression models to explore the driving factors of logistics facility location choice using a high-resolution grid-based data set. The results show that as the urban highway network gets improved, transportation costs are more balanced across space. Therefore, the distribution of logistics facilities is less regionally constrained and more widely located in space. The spatial evolution of logistics facilities was driven not only by demand of land uses and industries but also by transport supply and urban structure. Land use planning including the planning of industrial parks is among the important driving forces affecting the spatial location of logistics facilities, although the effects vary across types of logistics facilities. This study aims to provide a sustainable development-oriented policy path for regional development by proposing an analytical framework that reconsiders spatial location choice factors as a means of controlling logistics environmental negative externalities.